ANALYSIS OF CAESAREAN SECTIONS RATES USING ROBSON'S TEN GROUP CLASSIFICATION SYSTEM, UNIT B MCHC, ATH ABBOTTABAD - Sundus Ambreen Afridi,; Ahmad, Khalid; Ruqqiya Sultana , (Journal of Ayub Medical College Abbottabad, 2022)
Background: There is growing international concern about the increased rate of caesarean sections (CS), Caesarean procedures performed in the absence of a clinical justification do not reduce maternal or infant death rates if carried out at a rate higher than 10%-15% Achieving reductions in maternal and infant morbidity and mortality are, among others, the objectives promoted by the World Health Organization (WHO) for 2030. The analysis of unjustified C/S rate is done by Using Robson's Ten Group Classification system. Methods: Cross-sectional study by using Robson's Ten Group classification, in Unit B MCHC, ATH Abbottabad during 6 months, from 1st August 2021-31st January 2022. Results: Total Patients Delivered during this duration of study were 777, among which 352 were delivered by C/S were 352. Analysis by Robson ten-group classification system showed C/S Rate as: Group 1:16.81%, Group 2: 78.95%, group 3:1.56%, group 4:77.14%, group 5:89.22%, group 6: 83.33, Group 7:67.86, Group 8:40, group 9:100%, Group 10:46.97. The total Caesarean section rate was 45.3%. Conclusion: By RTGCS analysis, C/S rates Group 5, 4 and 2 are major contributions in overall C/S rates in studied clinical setup. Group 1 and 10 are also contributing. Overall C/S rates can be decreased by working on them.